The impact of firm size on the performance of trade in Serbia - Radojko Lukic (Economic and Environmental Studies (E&ES), 2015)
The impact of firm size on the economy and trade sector performance is lately researched due to its economic importance. Concerning it, this paper researches the specifics and determinants of impact of firm size on overall performance of distributive trade (wholesale and retail), with special insight on European Union and Serbia. Empirical research in the world, European Union and Serbia show very significant role of small and medium enterprises in creation of overall performance of trade sector, expressed through the number of enterprises, number of employees, turnover and added value. In that we find significant role of large trade chains which operate globally in many countries, including Serbia, which is a central issue in this paper.
Keywords: F65; L81; M40; 330; number and category of enterprise; employment; added value; measures and performance determinants; internationalization